Echinococcus multilocularis in Kyrgyzstan: similarity in the Asian EmsB genotypic profiles from village populations of Eastern mole voles (Ellobius tancrei) and dogs in the Alay valley. Issue 6 (November 2015) - Afonso, E.; Knapp, J.; Tête, N.; Umhang, G.; Rieffel, D.; van Kesteren, F.; Ziadinov, I.; Craig, P.S.; Torgerson, P.R.; Giraudoux, P.
Abstract Echinococcus multilocularis is a cestode that causes human alveolar echinococcosis, a lethal zoonosis of public health concern in central Asia and western China. In the present study, one of 42 Eastern mole voles (Ellobius tancrei) caught in Sary Mogol (Alay valley, southern Kyrgyzstan) presented liver lesions with E. multilocularis from which the EmsB target was amplified. The Asian profile obtained was almost identical to one amplified from domestic dog faeces collected in a nearby village. This observation adds additional information to the potential role of E. tancrei in the transmission of E. multilocularis, and to the known distribution range of E. multilocularis (Asian strain) in central Asia.